Uji Efektivitas Analgetik Dekokta Herba Rumput Bambu (Lophatherum Gracile Brongn.) Terhadap Mencit Putih Jantan (Mus Musculus) - Siti Aisyah Tanjung; M.Gunawan; Safriana Safriana (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2024)
Analgesics are compounds that in therapeutic doses relieve or suppress pain, without having general anesthetic action. Traditionally, the herb bamboo grass (Lophatherum gracile Brongn.) has been used and proven empirically to reduce pain, so it may have an analgesic effect. This can be caused by the content of secondary metabolite compounds, flavonoids, tannins, alkaloids, steroids/triterpenoids, saponins and glycosides, but this has not been scientifically proven. This research aims to determine the secondary metabolite compounds contained in fresh bamboo grass herbs, simplicia and dekokta and the effectiveness as an analgesic of the bamboo grass herb dekokta in mice.This research was carried out experimentally, including making simplicia and decoction, phytochemical screening and analgesic effectiveness testing. bamboo grass herb dekokta in male mice induced with 0.5% acetic acid intraperitoneally under the stomach, orally administered bamboo grass herb dekokta at a dose of 100 mg/kgBW, 200 mg/kgBW, 300 mg/kgBW, CMC 0.5% (blank), methampirone 65 mg/kgBB. Count the number of animal movements every 5 minutes for 1 hour. From the number of writhes obtained, the percentage of analgesic power and analgesic effectiveness were calculated. Next, the data obtained was analyzed statistically using SPSS ver.20 One Way ANOVA followed by the Tukey test. The results of the phytochemical screening of fresh bamboo grass, simplicia and dekokta contain alkaloids, flavonoids, tannins, saponins, steroids and glycosides. The greater the dose of bamboo grass herb dekokta given, the greater the percentage of reduction in writhing, so that the analgesic power and analgesic effectiveness are greater. . The results of the One Way ANOVA test and the Tukey test showed that the dose of 300 mg/kgBB had the best analgesic power at 50 minutes, not significantly different from administering 65 mg/kgBB of methampirone.